Profitabilitas, Operating Leverage, Ukuran Perusahaan Pertumbuhan Penjualan pada Struktur Modal Perusahaan Perbankan - Puspita, Kadek Angga Sintya; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 30 No 12 (2020), 2020)
This research was conducted to determine the effect of Profitability, Operating Leverage, Company Size and Sales Growth on the Capital Structure of Banking Companies. This research uses nonparticipant observation method. The sample used is 23 companies with a total sample of 115 observations in 5 years, through nonprobability sampling method with purposive sampling technique, and the number obtained is 115 observations. The data analysis technique used in this research is multiple linear regression analysis techniques. The results of this study indicate that profitability has a negative effect on the capital structure of banks. Operating leverage has a negative effect on the capital structure of banks. Firm size has a positive effect on banking capital structure. Sales growth has no effect on the banking capital structure. Keywords: Profitability; Operating Leverage; Company Size; Sales Growth.